2019
DOI: 10.1111/iwj.13038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social support and self‐efficacy on the psychosocial adjustment of Korean ostomy patients

Abstract: This study aims to test which factors influence and aid the psychosocial adjustment of patients with an ostomy and to provide data for the development of programmes for the self‐management of and psychosocial adjustment to intestinal stomas. A total of 150 ostomy patients were recruited between December 1, 2017 and March 26, 2018 in Korea and completed self‐report questionnaires. Data of 25 participants were excluded, resulting in a sample size of 125 participants. Factors, including social support subtypes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 25 publications
1
38
1
1
Order By: Relevance
“…Specifically, wives took more responsibility for taking care of patients in terms of their diet, appliance, and stoma than husbands; this fact has not been reported previously. The influence of collectivism and Confucianism, which emphasize family ties and the role of the household in South Korea, might explain this finding [ 38 ]. If patients’ families could not provide adequate care for male patients, they might be blamed by society.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, wives took more responsibility for taking care of patients in terms of their diet, appliance, and stoma than husbands; this fact has not been reported previously. The influence of collectivism and Confucianism, which emphasize family ties and the role of the household in South Korea, might explain this finding [ 38 ]. If patients’ families could not provide adequate care for male patients, they might be blamed by society.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐efficacy is also an important factor in the self‐care behaviours of colostomy patients. Indeed, self‐efficacy was found to increase when patients could independently perform self‐care (Nam et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 13 , 14 Social support has been identified as a critical factor for enhancing psychological adjustment, relieving the burden of living with an ostomy, and enhancing one’s sense of self-efficacy for ostomy management. 14 Indeed, CRC patients with poor social support experience increased difficulty adapting and adjusting to life with an ostomy and poor quality of life. 10 , 13 Similar to existing research on multiple types of cancer, 35 , 36 our study also found a strong association between social support and quality of life, especially in psychological and social well-being, in CRC patients with ostomies.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Given this theoretical framework and existing empirical evidence, the current study examined the moderating role of PTG in the relationship between social support and quality of life of CRC patients with ostomies. Considering that social support is an essential predictor of quality of life in this population, 14 the main research question focused on the potential moderating role of PTG in the relationship between social support and quality of life (Figure 1 ).…”
Section: Conceptual Modelmentioning
confidence: 99%